Habituation Is More Than Learning to Ignore: Multiple Mechanisms Serve to Facilitate Shifts in Behavioral Strategy. (19th August 2019) - McDiarmid, Troy A.; Yu, Alex J.; Rankin, Catharine H.
Abstract : Recent work indicates that there are distinct response habituation mechanisms that can be recruited by different stimulation rates and that can underlie different components (e.g., the duration or speed) of a single behavioral response. These findings raise the question: why is "the simplest form of learning" so complicated mechanistically? Beyond evolutionary selection for robustness of plasticity in learning to ignore, it is proposed in this article that multiple mechanisms of habituation have evolved to streamline shifts in ongoing behavioral strategy. Then, speculations are offered regarding the implications of this reconceptualization of habituation for approaching the analysis of mechanisms of more complex forms of learning and memory. Abstract : Multiple independent mechanisms of response habituation learning have recently been identified. In this article, it is proposed that these mechanisms serve to adaptively shift behavioral strategy. Then, speculations are offered regarding the importance of this reconceptualization of habituation for understanding neuropsychiatric disorders and more complex forms of learning and memory.